The Building Blocks of Antimicrobial Resistance in Pseudomonas aeruginosa: Implications for Current Resistance-Breaking Therapies - Langendonk, R. Frèdi; Neill, Daniel R.; Fothergill, Joanne L. (Frontiers in Cellular and Infection Microbiology, 2021)
P. aeruginosa is classified as a priority one pathogen by the World Health Organisation, and new drugs are urgently needed, due to the emergence of multidrug-resistant (MDR) strains. Antimicrobial-resistant nosocomial pathogens such as P. aeruginosa pose unwavering and increasing threats. Antimicrobial stewardship has been a challenge during the COVID-19 pandemic, with a majority of those hospitalized with SARS-CoV2 infection given antibiotics as a safeguard against secondary bacterial infection. This increased usage, along with increased handling of sanitizers and disinfectants globally, may further accelerate the development and spread of cross-resistance to antibiotics. In addition, P. aeruginosa is the primary causative agent of morbidity and mortality in people with the life-shortening genetic disease cystic fibrosis (CF). Prolonged periods of selective pressure, associated with extended antibiotic treatment and the actions of host immune effectors, results in widespread adaptive and acquired resistance in P. aeruginosa found colonizing the lungs of people with CF. This review discusses the arsenal of resistance mechanisms utilized by P. aeruginosa, how these operate under high-stress environments such as the CF lung and how their interconnectedness can result in resistance to multiple antibiotic classes. Intrinsic, adaptive and acquired resistance mechanisms will be described, with a focus on how each layer of resistance can serve as a building block, contributing to multi-tiered resistance to antimicrobial activity. Recent progress in the development of anti-resistance adjuvant therapies, targeting one or more of these building blocks, should lead to novel strategies for combatting multidrug resistant P. aeruginosa. Anti-resistance adjuvant therapy holds great promise, not least because resistance against such therapeutics is predicted to be rare. The non-bactericidal nature of anti-resistance adjuvants reduce the selective pressures that drive resistance. Anti-resistance adjuvant therapy may also be advantageous in facilitating efficacious use of traditional antimicrobials, through enhanced penetration of the antibiotic into the bacterial cell. Promising anti-resistance adjuvant therapeutics and targets will be described, and key remaining challenges highlighted. As antimicrobial stewardship becomes more challenging in an era of emerging and re-emerging infectious diseases and global conflict, innovation in antibiotic adjuvant therapy can play an important role in extending the shelf-life of our existing antimicrobial therapeutic agents.